Ursolic Acid Improves Intestinal Damage and Bacterial Dysbiosis in Liver Fibrosis Mice - Wan, Si-Zhe; Liu, Cong; Huang, Chen-Kai; Luo, Fang-Yun; Zhu, Xuan (Frontiers in Pharmacology, 2019)
Liver fibrosis is a reversible process of extracellular matrix deposition or scar formation after liver injury. Intestinal damage and bacterial dysbiosis are important concomitant intestinal changes in liver fibrosis and may in turn accelerate the progression of liver fibrosis through the gut-liver axis. RhoA, an important factor in the regulation of the cytoskeleton, plays an important role in intestinal damage. We investigated the effects of ursolic acid (UA), a traditional Chinese medicine with anti-fibrotic effects, on intestinal damage and bacterial disorder through the RhoA pathway. UA treatment reduced intestinal damage by inhibiting the inflammatory factor TNF-α and increased the expression of tight junction proteins and antibacterial peptides to protect the intestinal barrier. Moreover, the corrective effect of UA on bacterial dysbiosis was also confirmed by sequencing of the 16S rRNA gene. Potential beneficial bacteria, such as the phylum Firmicutes and the genera Lactobacillus and Bifidobacterium, were increased in the UA group compared to the CCl4 group. In liver fibrosis mice with RhoA inhibition via injection of adeno-associated virus, the liver fibrosis, intestinal damage and flora disturbances were improved. Moreover, UA inhibited the expression of RhoA pathway components. In conclusion, UA improves intestinal damage and bacterial dysbiosis partly via the RhoA pathway. This may be a potential mechanism by which UA exerts its anti-fibrotic effects and provides effective theoretical support for the future use of UA in clinical practice.